2008
DOI: 10.1080/10826080801914204
|View full text |Cite
|
Sign up to set email alerts
|

Listen to the Consumer: Designing a Tailored Smoking-Cessation Program for Women

Abstract: We used a consumer-driven approach to develop a model smoking-cessation program for women. Four focus groups (N = 23 [5-7/group]), each lasting 2 hours, were led by a professional moderator and audiotaped in 2004. Researchers reviewed transcripts; key themes were identified using scrutiny techniques (Ryan and Bernard, 2003). Necessary elements of a smoking-cessation program for women included support and choice (i.e., control over the program components), suggesting the need for an individualized program. Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Some of the themes that emerged here are consistent with findings in previous qualitative research. In one study, female veterans in the US also expressed a strong preference for both supportive services and having a choice of what services to use available when seeking smoking cessation treatment [ 25 ], confirming the importance of both of these features for women beyond the sample in the current study. Qualitative research with low-income women in Canada also identified several similar needs and preferences as reported here, including a “menu of support options” from which women could choose, child care onsite, free smoking cessation aids, and peer support opportunities (e.g., a “buddy”) [ 26 ].…”
Section: Discussionsupporting
confidence: 66%
“…Some of the themes that emerged here are consistent with findings in previous qualitative research. In one study, female veterans in the US also expressed a strong preference for both supportive services and having a choice of what services to use available when seeking smoking cessation treatment [ 25 ], confirming the importance of both of these features for women beyond the sample in the current study. Qualitative research with low-income women in Canada also identified several similar needs and preferences as reported here, including a “menu of support options” from which women could choose, child care onsite, free smoking cessation aids, and peer support opportunities (e.g., a “buddy”) [ 26 ].…”
Section: Discussionsupporting
confidence: 66%
“…Patients and communities can also play a key role in co‐designing the development and implementation of health promotion and prevention programs (S3). By collaborating with and empowering patients, patient advisory groups, communities and organizations, health‐care systems will be able to develop appropriate programs that meet the needs of all people . Building capacity of communities and organizations can also enhance integration, coordination and continuity of care, by supporting patients, and identifying resources that address barriers to accessing care and determinants of health (e.g housing, nutrition, education, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Although reasons for these differences have not been further investigated, they might reflect preferences as well as barriers in accessing these forms of cessation support. In general, women tend to prefer programs that prioritize support for women, and choice or control of program components (Katzburg, Farmer, Poza, & Sherman, 2008).…”
Section: Tailoring Approaches For Diverse Womenmentioning
confidence: 99%